Development and characterization of microsatellite loci for Cedrela fissilis Vell (Meliaceae), an endangered tropical tree species. - GANDARA, F. B. (2014)
The timber of the Neotropical tree Cedrela fissilis is used in construction, shipbuilding, carpentry and for medical purposes. In this study, polymorphic microsatellite (SSR) markers derived from an enriched genomic library were characterized using 120 adult trees from four different C. fissilis populations. No substantial genotypic linkage disequilibrium was detected among all possible pairs of SSR loci. The number of alleles per locus ranged from 2 to 20, the average allele number ranged from 8 to 9.7, depending on the population. The observed heterozygosity among the different SSR loci varied from 0.0 to 1.00 , the expected heterozygosity varied from 0.07 to 0.95 On the population level, the average observed and expected heterozygosities ranged from 0.50 to 0.63 and from 0.64 to 0.70, respectively. The average fixation index among populations ranged from 0.09 to 0.24. Thus, the SSR loci revealed high poly - morphism rates and can be used to study the genetic diversity,structure, mating system, and gene flow in C. fissilis.